Quick and easy method for determination of priority phenolic compounds in water and wastewater - Bhupander Kumar; Virendra Kumar Verma; Chandra Shekhar Sharma; Avinash B. Akolkar (MDPI AG, 2014)
Phenols and phenolic compounds are ubiquitous contaminants in the environment. Due to toxic potential, some phenolic compounds mainly chlorophenols and nitrophenols have been classified as priority pollutants. They enter into the environment through various sources such as industrial, domestic and vehicular emissions. For compliance of national and international regulations, various analytical methods have been developed for assessment in the environmental matrices. This paper presents quick, easy and reliable method for simultaneous determination of eleven priority phenolic compounds in wastewater using reversed-phase high-performance liquid chromatography and diode array detector. Liquid-liquid extraction technique with dichloromethane in acidic condition was used for the extraction, and chromatographic separation of compounds was carried out on a C18 column with water and methanol as the mobile phase. The following parameters like selectivity/ specificity, linearity (R2), range, limit of detection (LOD) and quantification (LOQ), precision (repeatability) and accuracy (recovery) were validated for consistent and reliable results. Calibration curves for all compounds were linear (R2, 0.998-0.999) within the concentration range of 5-125 (μg/mL). The LOD and LOQ of the method ranged between 0.11- 0.61 μg/L and 0.37-2.04 μg/L, respectively. This method was applied to quantify phenolic compounds in wastewater samples from urban drain with good separated peaks, precision and accuracy.